1988
DOI: 10.1002/jso.2930370105
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of carcinoembryonic antigen (CEA) in gastric tumors: Correlation with preoperative serum levels, histologic type, and grade of anaplasia of the tumor

Abstract: The occurrence of carcinoembryonic antigen (CEA) was studied in 45 cases of gastric tumors by the immunoperoxidase technique. CEA-positive staining was found in 48.8% of tumors. A correlation was found between preoperative CEA values and tumor CEA staining. All patients with serum CEA values below 2.5 ng/ml showed CEA-negative staining of tumor. In patients with serum CEA values between 2.6 and 10 ng/ml, the tumors showed a minority of CEA-positive cells; but in patients with serum CEA values above 10 ng/ml, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
3
12
1
Order By: Relevance
“…In in vivo experiments, the serum collected from peripheral blood of HMGC mice was directly qualified for CEA levels, as in a clinical examination in human patients. 25,26 ␤-Galactosidase Enzyme Reporter Assay. The activity of ␤-galactosidase enzyme in gastric cancer cells was measured according to the manufacturer's protocol (Promega, Tokyo, Japan) at 48 hours after infection with each Ad-LacZ at a multiplicity of infection (MOI) of 30.…”
Section: Methodsmentioning
confidence: 99%
“…In in vivo experiments, the serum collected from peripheral blood of HMGC mice was directly qualified for CEA levels, as in a clinical examination in human patients. 25,26 ␤-Galactosidase Enzyme Reporter Assay. The activity of ␤-galactosidase enzyme in gastric cancer cells was measured according to the manufacturer's protocol (Promega, Tokyo, Japan) at 48 hours after infection with each Ad-LacZ at a multiplicity of infection (MOI) of 30.…”
Section: Methodsmentioning
confidence: 99%
“…A few reports have shown a significant association between elevated CEA and peritoneal metastases [18,34]. Although several reports showed that elevated CEA was significantly associated with differentiated tumor types [7,10,48,61], a few reports indicated an association with poorly differentiated types of tumors [29]. Maehara et al analyzed the CEA levels in 221 patients with welldifferentiated gastric cancer.…”
Section: Ceamentioning
confidence: 99%
“…Serum CEA values correlate with disease stage and have a prognostic value and utility in staging for patients with gastrointestinal cancer, as based on univar iate analyses [ 1,15,16]. Serum CEA levels are influenced by a number of factors, including the level of CEA produc tion by the tumor cells, tumor volume, transport of CEA from the tumor into the systemic circulation, anatomical location of the tumor and the rate of metabolism of CEA in the liver [5], Santeusanio et al [17] reported that the rate of CEA production by the tumor itself is the major factor determining the serum CEA level, and a high per centage of CEA-positive tumors were noted in differen tiated gastric cancers. Findings were similar in differen tiated colon and pancreatic cancers [18], Rognum et al [19] reported that plasma CEA levels were higher in the colorectal cancers with aneuploid DNA; hence, aneuploid tumors may be more active than diploid ones as 'secretors' of CEA.…”
Section: Discussionmentioning
confidence: 99%